The Effect of Capital Structure, Institutional Ownership, Liquidity, and Diversification Strategy on Financial Performance - Astria Kurniawati; Sri Wahyuni; Azmi Fitriati; Nur Isna Inayati (Indonesian Journal of Business Analytics, 2022)
Financial performance is one of the factors to measure the success of a company. This study aims to examine the effect of capital structure, institutional ownership, liquidity and diversification strategies on financial performance. The population in this study are industrial sector companies listed on the IDX for the 2019-2021 period. The sampling method was carried out by purposive sampling and obtained 59 research samples. Methode of data analysis using multiple linear regression analysis. The results of the analysis carried out by capital structure, institutional ownership, and liquidity have a significant negative effect on financial performance, while the diversification strategy has no effect on financial performance. The results of this study can provide a scientific contribution in the field of accounting regarding the factors that influence financial performance.